Development of Radiopharmaceuticals for NPY Receptor-5 (Y5) Nuclear Imaging in Tumors by Synthesis of Specific Agonists and Investigation of Their Binding Mode - Bodin, Sacha; Peuker, Lisa C; Jestin, Emmanuelle; Alves, Isabel D; Velasco, Valérie; Ait-Arsa, Imade; Schollhammer, Romain; Lamare, Frédéric; Vimont, Delphine; MacGrogan, Gaétan; Hindié, Elif; Beck-Sickinger, Annette G; et al. (Bioconjugate chemistry, 2023)
The neuropeptide-Y (NPY) family acts through four G protein-coupled receptor subtypes in humans, namely, Y , Y , Y , and Y . A growing body of evidence suggest the involvement of the NPY system in several cancers, notably the Y subtype, thus acting as a relevant target for the development of radiopharmaceuticals for imaging or targeted radionuclide therapy (TRT). Here, the [cPP(1-7),NPY(19-23),Ala ,Aib ,Gln ]hPP scaffold, further referred to as sY ago, was modified with a DOTA chelator and radiolabeled with Ga and In and investigated and using the MCF-7 model. For studies, MCF-7 cells were orthotopically implanted in female nude mice and imaging with small animal positron emission tomography/computed tomography (μPET/CT) was performed. At the end of imaging, the mice were sacrificed. A scrambled version of sY ago, which was also modified with a DOTA chelator, served as a negative control (DOTA-[Nle]sY ago_scrambled). sY ago and DOTA-sY ago showed subnanomolar affinity toward the Y (0.9 ± 0.1 and 0.8 ± 0.1 nM, respectively) and a single binding site at the Y was identified. [ Ga]Ga-DOTA-sY ago and [ In]In-DOTA-sY ago were hydrophilic and showed high specific internalization (1.61 ± 0.75%/10 cells at 1 h) and moderate efflux (55% of total binding externalized at 45 min). On μPET/CT images, most of the signal was depicted in the kidneys and the liver. MCF-7 tumors were clearly visualized. On biodistribution studies, [ Ga]Ga-DOTA-sY ago was eliminated by the kidneys (∼60 %ID/g). The kidney uptake is Y -mediated. A specific uptake was also noted in the liver (5.09 ± 1.15 %ID/g vs 1.13 ± 0.21 %ID/g for [ Ga]Ga-DOTA-[Nle]sY ago_scrambled, < 0.05), the lungs (1.03 ± 0.34 %ID/g vs 0.20 %ID/g, < 0.05), and the spleen (0.85 ± 0.09%ID/g vs 0.16 ± 0.16%ID/g, < 0.05). In MCF-7 tumors, [ Ga]Ga-DOTA-sY ago showed 12-fold higher uptake than [ Ga]Ga-DOTA-[Nle]sY ago_scrambled (3.43 ± 2.32 vs 0.27 ± 0.15 %ID/g, respectively, = 0.0008) at 1 h post-injection. Finally, a proof-of-principle tissular micro-imaging study on a human primary cancer sample showed weak binding of [ In]In-DOTA-sY ago in prostatic intra-neoplasia and high binding in the ISUP1 lesion while normal prostate was free of signal.